Effectiveness Analysis of Peduli Lindungi in Community Activities Restrictions during The Covid-19 Pandemic - Ika Zulkafika Mahmudah; Evi Susanti; Ahmad Faiz Muhammad Noer; Suko Widodo (Jurnal Spektrum Komunikasi, 2022)
The government has intensified the use of the Peduli Lindungi application in limiting community activities. However, until now, academically, there has been no research related to the effectiveness of Peduli Lindungi. This research aims to analyze the effectiveness of utilizing the Peduli Lindungi Application to organize social activities. The research design used descriptive quantitative with google form instrument filled by 130 respondents used Peduli Lindungi which are spread all over Indonesia. Based on component system quality, Information quality, Service quality, user intention, user satisfaction, and the net benefit listed in the questionnaire, user effectiveness is more than 70% which can be called effective. Peduli Lindungi Application is a newly growing application that presents a mapping case Covid-19, but that application provides many features that support health service and travel planning with restricted activities. There is no value effectiveness more than 80% indicate to required to meet society’s needs. Application development with more complete and interactive facilities is needed. Regular evaluation and two-way communication service system of application features will be more interesting for presenting the information.